2018
DOI: 10.1038/s41598-018-30614-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of heterostructures based on transition metal dichalcogenides and graphene-like zinc oxide

Abstract: The structural, electronic, and optical properties of heterostructures formed by transition metal dichalcogenides MX2 (M = Mo, W; X = S, Se) and graphene-like zinc oxide (ZnO) were investigated using first-principles calculations. The interlayer interaction in all heterostructures was characterized by van der Waals forces. Type-II band alignment occurs at the MoS2/ZnO and WS2/ZnO interfaces, together with the large built-in electric field across the interface, suggesting effective photogenerated-charge separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(126 citation statements)
references
References 56 publications
9
110
0
Order By: Relevance
“…This indicates that more photogenerated carriers can be shared between HfS 2 and MoTe 2 aer photoexcitation. 55 As shown at the bottom of Fig. 6(b), charge accumulation occurs mainly in the middle of the interface, while charge depletion occurs on the surface of In heterostructure, the wave function mixing in HfS 2 /MoTe 2 is higher with the enhancement of interlayer interaction.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 90%
“…This indicates that more photogenerated carriers can be shared between HfS 2 and MoTe 2 aer photoexcitation. 55 As shown at the bottom of Fig. 6(b), charge accumulation occurs mainly in the middle of the interface, while charge depletion occurs on the surface of In heterostructure, the wave function mixing in HfS 2 /MoTe 2 is higher with the enhancement of interlayer interaction.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 90%
“…However, noble metals are expensive and not viable for large-scale production. Among the various candidates, transition metal dichacogenides (TMD) materials have attracted significant attention due to its unique physical, optical, and electrical properties [7,8]. The lack of dangling bond of the basal plane layer enables the photovoltage (V ph ) be governed by the solid-state junction rather than its surface [9], which gives interest to many researchers to exploit the material to adapt in the field of photoelectrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…39 2D ZnO is known to be an environmentally friendly material, which has been successfully synthesized in experiments, [40][41][42] making it a desirable material for fabricating highefficiency photovoltaic and optoelectronic nanodevices. To date, vdWHs made by stacking ZnO monolayers on top of another 2D material have been proposed and widely investigated, such as ZnO/phosphorene, 43,44 ZnO/TMDs, [45][46][47] ZnO/BSe, 48 and ZnO/ GaN. 49 These investigations demonstrated that 2D ZnO can be considered as an ideal material for constructing vdWHs.…”
Section: ) or Selenization Of Mos 2 33mentioning
confidence: 99%
“…They demonstrated that the ZnO/BSe vdWH is a promising material for water splitting because it possesses a type-II band alignment with high carrier mobility and enhanced optical absorption. Wang et al 45 studied several kinds of ZnO/TMDs vdWHs, including ZnO/MX 2 (M ¼ Mo, W; X ¼ S, Se) and demonstrated that all these vdWHs display excellent optical absorption, which merits optical and photovoltaic applications.…”
Section: ) or Selenization Of Mos 2 33mentioning
confidence: 99%